NEW GEOLOGIC, PETROLOGIC AND MINERALOGIC DATA ON THE MESOZOIC HIGH-PRESSURE ROCK ASSOCIATION OF SAKHALIN - Biryukov V.M.; Kosygin Y.A.; Bekhtol'd A.F.; Semenov D.F. (My University, 1988)
The high-pressure rock association in one area of Sakhalin is described. Within the area studied, the high-pressure association forms a sublatitudinally oriented zone, 300 to 500 m wide and composed mainly of alternating lenticular bodies of amphibolite, metagabbro and serpentinized ultramafic rock. The amphibolite-ultramafic rock contacts are everywhere tectonic. The fault planes are both steep (<85°) and gentle (40° to subhorizontal). The ultramafic bodies range in thickness from several meters to 200 m. Amphibolite beds are as thick as 150 m. Eclogitic rocks, the most interesting in this association, lie among metamafic varieties as indistinct lenses and segregations, ranging in width from fractions of a meter to several meters. These rocks consist chiefly of clinopyroxene (30 to 70 vol. percent), garnet (≤25) and quartz (≤70) and also contain chlorite, amphibole, stilpnomelane, albite, sphene and apatite. The latest mineral is quartz, which in many places forms veinlets cutting crystals of pyroxene and, less commonly, garnet.
Keywords: Mesozoic; Mesozoic; Мезозой